Water resources management – Nature protection – Land use - Horoszné Gulyás, Margit (Acta Agraria Kaposváriensis, 2007)
Water is life. There are many problems with the water quality and quantity and the water requirement is increasing. The Water Framework Directive will impact on every aspect of water use: domestic, industrial, agricultural, leisure and environmental conservation. Besides restrictions on point source discharges, the achievement of good status will mean tackling the problem of diffuse pollution from agriculture and contaminated land. Environmental organisations hope that implementation of the Directive will result in major improvements to the biodiversity of water habitats. The aim of the project WAREMA is to discuss this problems with the stakeholders and together make an integrated spatial planning concept.